IMPACT OF DIABETES ON LONG-TERM OUTCOMES IN STEMI PATIENTS UNDERGOING PRIMARY ANGIOPLASTY WITH GLYCOPROTEIN IIB-IIIA INHIBITORS AND BARE METAL STENTS (BMS) OR DRUG-ELUTING STENTS (DES) - KHAN, RD; MAQSOOD, S; KHAN, MA; ALI , N; KHAN, IU; AHMAD, Z (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to investigate the impact of diabetes on long-term outcomes in STEMI patients undergoing primary angioplasty with glycoprotein IIb/IIIa inhibitors and either BMS or DES. The study was conducted at the interventional cardiology department of HMC and included 278 patients between March 6, 2022, and September 5, 2022. Inclusion criteria were STEMI patients undergoing primary angioplasty, while exclusion criteria were patients with chronic total occlusion, left main disease, and previous PCI or CABG. Data collection was done through chart review and patient follow-up for one year. Diabetic patients had a higher incidence of multivessel disease, and there was a trend towards a higher rate of Major-adverse-cardiac-events (MACE) and Target Vessel Revascularization (TVR) at long-term follow-up. Drug-eluting stents (DES) were associated with a lower TVR incidence than BMS. Our study highlights the negative impact of diabetes on long-term outcomes in STEMI patients undergoing primary angioplasty with glycoprotein IIb/IIIa inhibitors and either BMS or DES. Further studies are needed to confirm these findings and explore potential mechanisms underlying the adverse cardiovascular outcomes in diabetic patients with STEMI. Ultimately, improving the care of diabetic patients with STEMI is critical to reducing morbidity and mortality in this high-risk population.